’Dino, Mirko, Afro Basaldella’ a Udine. Storia di una mostra tra museo e spazio urbano - Cortes Casarrubios, William (Opus Incertum, 2024)
In 1987, the significant retrospective exhibition held in Udine and titled Dino, Mirko, Afro Basaldella marked the rediscovery of the three Basaldella brothers within the context of 20th-century European art. Curated primarily by the sculpture historian Enrico Crispolti, the exhibition sought to comprehensively reassess the careers of the three artists. Enrico Crispolti leveraged his expertise in public art exhibitions to orchestrate an event that engaged the entire historical context of the city, spanning from the Castle – the main venue – to the Gallery of Modern Art. The exhibition design was overseen by the renowned local architectural studio of Gianni and Elena Avon. Together, Avon and Crispolti endeavored to transform Udine into an ’open-air museum,’ integrating the Basaldella brothers’ works with the city’s historical architecture and existing monuments. Additionally, the exhibition featured other works by the same artists, such as the Monumento alla Resistenza designed by Gino Valle, which included a prominent sculpture by Dino Basaldella. This event not only offered Crispolti an opportunity to experiment with new methods of showcasing open-air sculptures but also constituted an important moment in the contemporary art history of Udine.